Congenital hypovitaminosis A in dairy cattle - Sosa, Emiliano; Morrell, Eleonora Lidia; Llada, Ignacio Mariano; Odriozola, Ernesto Raul; Canton, German Jose (British Veterinary Association, 2023)
Hypovitaminosis A negatively impacts the health of ruminants feeding on low-fresh forage diets for long periods of time. Although this disease is characterised by different clinical presentations, its congenital form is underreported. Here, we describe an outbreak of vitamin A deficiency that affected 30% of calves born in a dairy heifer herd. At birth, the affected animals showed weakness, ataxia, mydriasis, bluish coloration of the tapetum lacidum and blindness as the main clinical signs. The gross pathological findings at postmortem examination revealed cerebellar herniation, flattened gyri and narrowed sulci of the cerebral cortex in an affected calf. Histopathology showed squamous metaplasia of the efferent ducts in the parotid gland and hyperkeratosis of the ruminal mucosa. In addition, the plasma levels of vitamin A in the heifers and calves were below the reference values. These results confirmed the first reported case of congenital hypovitaminosis A in cattle in Argentina.